2020
DOI: 10.1111/2041-210x.13356
|View full text |Cite
|
Sign up to set email alerts
|

The neglected impact of tracking devices on terrestrial arthropods

Abstract: Tracking devices have become small enough to be widely applied to arthropods to study their movement. However, possible side effects of these devices on arthropod performance and behaviour are rarely considered. We performed a systematic review of 173 papers about research in which tracking devices—radio frequency identification (RFID), harmonic radar and radio telemetry tags—were attached to terrestrial arthropods. The impact of such tags was quantified in only 12% of the papers, while in 40% the potential im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 71 publications
4
54
0
Order By: Relevance
“…We further investigated the potential influence of the tag's weight on beetles, and found that body/tag mass ratio was 14 % in average (Table 1) which is far below as it was in previous findings for the same species (50 % in Riecken and Raths 1996). Although there is no direct suggestion for body/tag mass ratio for walking insect, a recent study suggests 23-33 % limits for these thresholds for flying species (Batsleer et al 2020), thus we believe that tags used in this study apparently did not bias beetles' movement. Although we tagged only six individuals, we found that the quality of the data is suitable to draw relevant consequences.…”
Section: Radio-tracking Of Ground Beetlesmentioning
confidence: 58%
“…We further investigated the potential influence of the tag's weight on beetles, and found that body/tag mass ratio was 14 % in average (Table 1) which is far below as it was in previous findings for the same species (50 % in Riecken and Raths 1996). Although there is no direct suggestion for body/tag mass ratio for walking insect, a recent study suggests 23-33 % limits for these thresholds for flying species (Batsleer et al 2020), thus we believe that tags used in this study apparently did not bias beetles' movement. Although we tagged only six individuals, we found that the quality of the data is suitable to draw relevant consequences.…”
Section: Radio-tracking Of Ground Beetlesmentioning
confidence: 58%
“…The reality that individual studies of device effects typically have low power places an increased focus on the results of meta‐analyses as a means of understanding the impacts of device attachment. Fortunately, a range of such studies are available to aid the development of tagging studies across multiple animal groups (Barron et al., 2010; Batsleer et al., 2020; Matthews et al., 2013). One of the main justifications for conducting a meta‐analysis is to increase statistical power (Cohn & Becker, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Threshold rules are often not considered for invertebrates, with insect biologgers weighing anything from 2% to 100% of the insect's body mass (Kissling, Pattemore, & Hagen, 2014). Few studies have examined the impacts on insect welfare, particularly regarding the energetic costs of carrying such loads and impacts on social behaviour and survival (12% studies quantified impact: Batsleer et al., 2020). Tagged individuals are often the largest in the population and have better inherent survival (Le Gouar, Dubois, Vignon, Brustel, & Vernon, 2015), but further research is needed to fill the knowledge gap and inform best practice (Batsleer et al., 2020).…”
Section: Welfare Considerations In Capturing Handling and Housing Ofmentioning
confidence: 99%
“…Few studies have examined the impacts on insect welfare, particularly regarding the energetic costs of carrying such loads and impacts on social behaviour and survival (12% studies quantified impact: Batsleer et al., 2020). Tagged individuals are often the largest in the population and have better inherent survival (Le Gouar, Dubois, Vignon, Brustel, & Vernon, 2015), but further research is needed to fill the knowledge gap and inform best practice (Batsleer et al., 2020). Additionally, for all species, it is important to consider the standard fluctuations in body mass that individuals may experience even within relatively short time‐scales (e.g.…”
Section: Welfare Considerations In Capturing Handling and Housing Ofmentioning
confidence: 99%